Reproductive Outcomes and Endocrine Profile in Artificially Inseminated versus Embryo Transferred Cows - Jordana S. Lopes; Estefanía Alcázar-Triviño; Cristina Soriano-Úbeda; Meriem Hamdi; Sebastian Cánovas; Dimitrios Rizos; Pilar Coy (Animals, 2020)
The increasing use of in vitro embryo production (IVP) followed by embryo transfer (ET), alongside with cryopreservation of embryos, has risen concerns regarding the possible altered pregnancy rates, calving or even neonatal mortality. One of the hypotheses for these alterations is the current culture conditions of the IVP. In an attempt to better mimic the physiological milieu, embryos were produced with female reproductive fluids (RF) as supplements to culture medium, and another group of embryos were supplemented with bovine serum albumin (BSA) as in vitro control. Embryos were cryopreserved and transferred while, in parallel, an in vivo control (artificial insemination, AI) with the same bull used for IVP was included. An overview on pregnancy rates, recipients’ hormonal levels, parturition, and resulting calves were recorded. Results show much similarity between groups in terms of pregnancy rates, gestation length and calves’ weight. Nonetheless, several differences on hormonal levels were noted between recipients carrying AI embryos especially when compared to BSA. Some calving issues and neonatal mortality were observed in both IVP groups. In conclusion, most of the parameters studied were similar between both types of IVP derived embryos and the in vivo-derived embryos, suggesting that the IVP technology used was efficient enough for the safe production of calves.